Estudo da utilização do extrato aquoso de barbatimão (Stryphnodendron barbatimão, M.) no ensino de química - PINHEIRO, Marta Helena Tavares (2014)
In the present work, the pH dependent colour change of the crude vegetal extracts is suggested in teaching chemical or acid-base equilibria, visual indicators and some aspects of spectrophotometric concepts its applications. The extraction methodology proposed is inexpensive and easy to perform in secondary schools and in general chemistry or instrumental undergraduate courses.